Socialization of Making Cookies Containing Moringa Leaf Extract (Moringa oleifera L.) to Help Prevent Stunting - Indrasari, Ferika; Akbar, Nanda Dwi; Leki, Karol Giovani Batista; Shifa, Ayu Atsna (Sarana Ilmu Indonesia (salnesia), 2025)
The stunting rate among toddlers in Semarang City is 2,73%, consisting of 0,26% very short toddlers and 2,47% short toddlers. Although this prevalence is relatively low, continuous prevention and management efforts are still required to further reduce stunting cases. One local food ingredient with high nutritional potential is Moringa leaves (Moringa oleifera L.), which are rich in protein, vitamins, and minerals. Moringa leaves can be processed into various food products, including cookies. Cookies are a popular snack consumed by all age groups and have high energy content, making them suitable as complementary foods for toddlers. This community service activity aimed to increase public knowledge regarding the utilization of moringa leaf cookies as a stunting prevention strategy. The activity was conducted under the theme “Socialization of Making Cookies from Moringa Leaf Extract (Moringa oleifera L.) to Help Prevent Stunting.” A total of 50 PKK mothers participated from Bulu Lor Village, North Semarang, who participated in the activity. The intervention consisted of a 30-minute educational session using visual media, including pictures and PowerPoint presentations. Participants completed pre-test and post-test questionnaires that met validity and reliability standards. Data were analyzed univariately. The results showed that cookies with small amounts of moringa leaf powder were acceptable in taste and not bitter. Knowledge levels increased across all cognitive domains. Statistical analysis using a t-test indicated a significant difference between pre-test and post-test scores (p-value = 0,003). In conclusion, the activity effectively improved participants’ knowledge of using moringa leaf cookies to prevent stunting in toddlers.